Voices and lived experiences of perinatal women recovering from mental illness and informal caregivers regarding quality of maternal mental health care in south western Uganda - Gladys Nakidde; Ronald Kamoga; John F. Mugisha; Edward Kumakech (Discover Mental Health, 2026)
Abstract Background Maternal mental illness (MMI) contributes significantly to maternal morbidity, particularly in low-resource settings. Although policies support integrating maternal mental health into routine maternity care, assessments of care quality have largely focused on health workers’ perspectives rather than women’s lived experiences. This study explored the quality of maternal mental health care as experienced by women recovering from MMI and family caregivers. Methods A phenomenological qualitative study was conducted between November 2022 and February 2023. Nineteen participants were purposively recruited from two regional referral hospitals in southwestern Uganda. We included women who had recovered from MMI and family caregivers. Following REC and hospital approvals, participants were contacted by telephone and after consent, appointments for the interviews were scheduled. Data were collected using in-depth interview guide until saturation was reached and manual thematic analysis done, guided by a hybrid coding approach. Results Most participants were female with male caregivers being husbands, rural residents, and self-employed. Women were aged 23–37 and caregivers 28–65 years. Five interrelated themes emerged: perceived causes of MMI; clinical presentation and healthcare experiences; challenges, recommendations, and future hopes; community perceptions and stigma; and social support and family dynamics. These inform that sociocultural beliefs, health-system responsiveness, and family support shape perceptions of care quality. Recovery and satisfaction were mainly attributed to hospital-based mental health services, often accessed through self-referral after maternity discharge. Conclusion Despite some positive experiences, maternal mental health care quality remained limited by experienced challenges. Interventions should focus on community education, integrating mental health screening and management into maternity services, improving medicine availability and addressing stigma through culturally appropriate approaches.